2021
DOI: 10.1200/op.20.00441
|View full text |Cite
|
Sign up to set email alerts
|

Provider-Level Variation in Treatment Planning of Radiation Oncology Procedures in the United States

Abstract: PURPOSE: Variation in the use of radiation oncology procedures and technologies is poorly characterized. We sought to identify associations between the treatment planning codes used to bill for radiotherapy procedures and the demographic characteristics of the radiation oncologists submitting them. METHODS: The Physician and Other Supplier Public Use File was linked to the Physician Compare database by using the physician National Provider Identifier for the year 2016. Analysis was stratified by practice setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…With regard to physician gender as a predictor of RT procedure use, an earlier study highlighted significant gender differences in the use of radiotherapy treatment planning codes, 13 whereas our analysis of treatment delivery codes did not reveal any significant gender differences other than with regard to use of LDR brachytherapy. A likely explanation for these disparate findings lies in the distinction between RT planning and delivery codes.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…With regard to physician gender as a predictor of RT procedure use, an earlier study highlighted significant gender differences in the use of radiotherapy treatment planning codes, 13 whereas our analysis of treatment delivery codes did not reveal any significant gender differences other than with regard to use of LDR brachytherapy. A likely explanation for these disparate findings lies in the distinction between RT planning and delivery codes.…”
Section: Discussioncontrasting
confidence: 76%
“…The latter may consequentially abrogate any gender distinctions in the utilization of specific procedures. We also note that unlike the previously published RT planning analysis, 13 the present study excluded providers in facility-based practices where technical billing is not allowed. Thus, when considering the larger national population of radiation oncologists, there may in fact exist gender differences in the delivery of RT procedures that our study was unable to capture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although overall receipt and timing of radiation therapy did not differ across the rural-urban continuum, we found the use of IMRT varied across geography, as reported in other settings. 26 , 27 Nonetheless, the routine use of IMRT for rectal cancer remains a source of ongoing controversy in the radiation oncology community 28 , 29 and recent guidelines do not recommend it given mixed efficacy data 30 , 31 , 32 despite dosimetric studies showing reduced dose to small bowel, bladder, and bone marrow. 33 , 34 , 35 , 36 Similarly, we found that surgeon training and surgical modality varied across geography, with rural and small town patients least likely to receive care from subspecialty-trained surgeons or minimally invasive surgical approaches, trends observed in other disease settings.…”
Section: Discussionmentioning
confidence: 99%